Coorg, Report and Tables, Vol-XIII - Mandanna, M.S. (Karnataka, 1931)
Distribution and movement of population, Urban and Rural population, Birthplace and Migration, Age, Sex, Civil Condition, Infirmities, occupation, literacy, languages, Religion, Race, caste or tribe, Imperial Tables, Provincial Tables.
Keywords: Coorg; Report and Tables